Witnesses to the Baptist heritage: thirty Baptists every Christian should know - Williams, Michael E. (The James N. Griffith series in Baptist studies, 2015)
Baptists lack a single central figure in their origins that Lutherans, Reformed, Presbyterians, and Methodists have with Martin Luther, John Calvin, John Knox, and John Wesley. Additionally, Baptists focus so heavily on the Bible for authority and key beliefs or practices like religious liberty, social justice, missions, and preaching that sometimes Baptists and other Christians forget the significant role that people play in forging and promoting those ideas and practices. This book seeks to address this shortcoming by providing an introductory text of Baptist biographies